Development of a Parallel and Indirectly Self-adaptive Robot Hand with Single-chain Transmission of Double-rack Mechanism - Jingwei Su; Wenzeng Zhang (Jixie chuandong)
Traditional robot fingers with parallel and self-adaptive hybrid grasping mode have double-chain transmission mechanisms， which have disadvantages of complexity in mechanisms. A novel design of a parallel and indirectly self-adaptive underactuated robot finger with a single chain transmission mechanism， called PISA hand is presented. The method uses three gears， two racks， a slider， a block， a limit and a spring to achieve using a single motor to drive two phalanges. The PISA finger can realized the pinching grasp with the distal phalanx and enveloping grasp with the proximal phalanx with a slider and the distal phalanx. The composition and movement process of the PISA finger are introduced in detail. Theoretical analysis of the range and grasping force are given. Simulation and experimental results show that the PISA finger can automatically switch the grasping modes according to the different positions and shapes of the object so as to achieve stable grasping. The PISA hand has high transmission efficiency， compact structure.